Efecto de la inclusión de medicago sativa sobre los parámetros productivos e indicadores organolépticos de la canal de pollos broiler - Chuquisala Pinza, Diana Veronica (Machala : Universidad Técnica de Machala, 2019)
The present research work was carried out in the farm Santa Inés of the Academic Unit of Agricultural Sciences (UACA) of the Technical University of Machala in the Province of El Oro, the objective was the effect of the inclusion of Medicago sativa on the Productive parameters and organoleptic indicators of the chickens chicken channel. A Completely Randomized Design (DCA) is applied, using 200 Cobb 500 mixed chickens, applying the poultry biosecurity rules for open-house systems, five experimental groups are randomly distributed (T1 = Control, T2 = inclusion of the flour from Medicago sativa 1% to the balanced formula, T3 = inclusion of Medicago sativa flour at 2% to the balanced formula, T4 = inclusion of Medicago sativa flour at 3% to the balanced formula and T5 = inclusion of Medicago sativa flour at 4% to the balanced formula, each with four experimental units 10 chickens each (40 birds per treatment) To standardize the research work, a BALMAR commercial balance must be carried out, which has been acquired in a balanced plant in the Canton Balsas of the Province of El Oro. For this, all the stages are included (Pre-Initial, Initial, Fattening and Completion) with the respective differences of substitution in the addiction to the percentages of alfalfa flour. The variables evaluated were: live weight of the animal, consumption of food measured in grams, water consumption, feed conversion, mortality and organoleptic indicators (weight of the channel and sensory analysis). Sensory analysis was carried out the odor, taste, tenderness and juiciness tests, for this 35 days were slaughtered 40 animals taken at random and slaughtered by cervical dislocation, two chickens per experimental unit obtaining live weight data, weight bled, weight without feathers, weight without viscera, weight without head - neck and legs, weight of breast, weight of frozen breast and thickness of abdominal fat. For the weight data, a CAMRY brand scale balance with a capacity of 5 kg was used, with an error margin of ± 1 g, the volume data were recorded with a 4 liters capacity container with minimum measurements of 50 ml. To obtain abdominal fat thickness data, a 0-150 mm digital foot caliper (TACTIX brand) was used. Consumer surveys were conducted at the UACA, where students, teachers and administrative staff participated. An analysis was used for one factor (ANOVA) in all the variables studied, to discriminate the means the Fisher's LSD procedure was used, with a confidence level of 95.0% in the statistical program STATGRAPHICS Centurión XV.I. and according to the results obtained, it is concluded that when comparing the different treatments with the control group on the live weight, food and water consumption, feed conversion and mortality, it does not show an effect in them, so the alfalfa can be used at 4% without problem, besides it does not show a effect on the productive performance parameters, does not influence the abdominal fat thickness or the organoleptic characteristics of the meat.
El presente trabajo de investigación se realizó en la granja Santa Inés de la Unidad Académica de Ciencias Agropecuarias (UACA) de la Universidad Técnica de Machala en la Provincia de El Oro, el objetivo fue evaluar el efecto de la inclusión de Medicago sativa sobre los parámetros productivos e indicadores organolépticos de la canal en pollos broilers. se utilizó un Diseño Completamente al Azar (DCA), empleando para ello 200 pollos Cobb 500 mixtos, aplicando las normas de bioseguridad avícola para sistemas de naves abiertas, se distribuyó al azar cinco grupos experimentales (T1= Testigo, T2= inclusión de la harina de Medicago sativa al 1% a la fórmula balanceada, T3= inclusión de harina Medicago sativa al 2% a la fórmula balanceada, T4= inclusión de harina de Medicago sativa al 3% a la fórmula balanceada y T5= inclusión de harina Medicago sativa al 4% a la fórmula balanceada), cada uno con cuatro unidades experimentales 10 pollos cada una (40 aves por tratamiento). Para estandarizar el trabajo de investigación se utilizó balanceado comercial BALMAR, el mismo que se adquirió en una planta de balanceados ubicada en el Cantón Balsas de la Provincia de El Oro. Para ello se usaron todas las etapas (Preinicial, Inicial, Engorde y Finalización) con las respectivas diferencias de sustitución al adicionar los distintos porcentajes de harina de alfalfa de acuerdo a su tratamiento. Las variables evaluadas fueron: Peso vivo del animal, consumo de alimento medido en gramos, consumo de agua, conversión alimenticia, mortalidad e indicadores organolépticos (peso de la canal y análisis sensorial). Dentro del análisis Sensorial se realizó las pruebas de olor, sabor, terneza y jugosidad, para ello al día 35 se faenaron 40 animales tomados al azar y sacrificados por dislocación cervical, dos pollos por Unidad experimental obteniendo datos de peso vivo, peso desangrado, peso sin plumas, peso sin vísceras, peso sin cabeza - cuello y patas, peso de pechuga, peso de pechuga congelada y espesor de grasa abdominal. Para los datos de peso se usó una balanza gramera marca CAMRY con capacidad de 5 Kg con un margen de error de ±1g, los datos de volumen se registraron con un envase de 4 litros de capacidad con medidas mínimas de 50 ml. Para obtener los datos de espesor de grasa abdominal se empleó un calibrador Pie de Rey digital 0-150 mm (Marca TACTIX). Las encuestas de consumidor se realizaron en la UACA, donde participaron estudiantes, docentes y personal administrativo. Se empleó un análisis para un factor (ANOVA) en todas las variables estudiadas, para discriminar las medias se empleó el procedimiento LSD de Fisher´s, con un nivel de confianza del 95,0% en el programa estadístico STATGRAPHICS Centurión XV.I. y de acuerdo a los resultados obtenido, se concluye que al comparar los distintos tratamientos con el grupo testigo sobre el peso vivo, consumo de alimento y agua, conversión alimenticia y mortalidad, no muestra efecto en éstos por lo que la alfalfa puede utilizarse al 4% sin problema, además no muestra un efecto en los parámetros productivos de rendimiento, no influye en el espesor de grasa abdominal ni sobre las características organolépticas de la carne.
Keywords: ALFARINA; GRASA; ABDOMINAL; ANÁLISIS